2003
DOI: 10.1002/ajmg.a.20188
|View full text |Cite
|
Sign up to set email alerts
|

657del5 mutation in the gene for Nijmegen breakage syndrome (NBS1) in a cohort of Russian children with lymphoid tissue malignancies and controls

Abstract: Nijmegen breakage syndrome (NBS, OMIM 251260) is a rare hereditary disease, characterized by immune deficiency, microcephaly, and an extremely high incidence of lymphoid tissue malignancies. The gene mutated in NBS, NBS1, was recently cloned from its location on chromosome 8q21. The encoded protein, nibrin (p95), together with hMre11 and hRad50, is involved in the double-strand DNA break repair system. We screened two Russian cohorts for the 657del5 NBS1 mutation and found no carriers in 548 controls and two c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 34 publications
1
22
1
Order By: Relevance
“…Although a number of published reports have suggested that mutations in NBS1, especially 657del5, is associated with elevated risk for some cancers, including ovarian (13), breast (7,8,10), melanoma (7,9), and lymphoid malignancies (7,11,12), such findings have not been replicated in other studies (21)(22)(23)(24). For prostate cancer, Cybulski et al (5) found that the 657del5 mutation was a risk factor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although a number of published reports have suggested that mutations in NBS1, especially 657del5, is associated with elevated risk for some cancers, including ovarian (13), breast (7,8,10), melanoma (7,9), and lymphoid malignancies (7,11,12), such findings have not been replicated in other studies (21)(22)(23)(24). For prostate cancer, Cybulski et al (5) found that the 657del5 mutation was a risk factor.…”
Section: Discussionmentioning
confidence: 99%
“…This founder mutation has been found with a high frequency in the Slavic population, which includes individuals primarily from Poland, Ukraine, and the Czech Republic. A number of studies suggest that heterozygosity for a mutation in NBS1 may be associated with elevated risk for some cancers (7)(8)(9)(10)(11)(12)(13), including prostate cancer (5). Cybulski et al (5) showed an increased risk for prostate cancer among carriers of the 657del5 mutation in both familial and non-familial cases from Poland.…”
Section: Introductionmentioning
confidence: 99%
“…A number of hypomorphic mutations in NBS1, MRE11 and RAD50 have been identified in patients with Nijmegen breakage syndrome (NBS), A-T-like disorder (A-TLD) and NBS-like disorder (NBSLD) respectively. Patients with these mutations show a phenotypic spectrum similar to other NHEJ disorders (microcephaly, immunodeficiency, radiosensitivity and cancer predisposition) with varying severity that may reflect the nature of the hypomorphic mutation on protein levels and DSB repair activity, or functional differences between these proteins [67][68][69][70][71][72].…”
Section: The Mrn Complex Nijmegen Breakage Syndrome and Ataxia Telanmentioning
confidence: 99%
“…NBS and AT patients are known to be radiosensitive. Studies have suggested that carriers of these diseases are also radiosensitive (Dumon-Jones et al 2003;Resnick et al 2003). However, these studies have been hampered by the lack of accurate assays to identify carriers.…”
Section: Discussionmentioning
confidence: 99%
“…A founder mutation, 657del5, was identified in many patients of Slavic descent; nevertheless, there are patients with other mutations in the nibrin gene (Varon et al 1998). Studies have shown that although NBS is an autosomal recessive disorder, heterozygous carriers have an increased risk of cancer and sensitivity to radiation (Dumon-Jones et al 2003;Resnick et al 2003;Cybulski et al 2004). While polymerase chain reaction with sequence-specific primers can reliably detect carriers of the common 657del5 mutations (Drabek et al 2002), it is not practical for identifying carriers of other nibrin mutations.…”
mentioning
confidence: 99%